2006
DOI: 10.1021/ie051160s
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Molecular Clustering of TIP4P and SPC/E Water Models from Higher-Order Virial Coefficients

Abstract: Higher-order virial coefficients (up to B 6 ) for TIP4P and SPC/E water models are used to characterize molecular clusters (up to hexamers) formed by water at various gas-phase thermodynamic state points between 298 and 773 K. Comparison of cluster statistics with available molecular simulation data for the same models indicates that the virial approach is effective at characterizing the clustering behavior. Significant deviations from experimentally confirmed ab initio results from the literature at 298 K are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 37 publications
0
49
0
Order By: Relevance
“…For example, including a three-body interaction term results in very good agreement for the thermodynamic properties of argon from near the critical point to twice the critical density (Leder, 1985). As was discussed by Benjamin et al (2006Benjamin et al ( , 2007aBenjamin et al ( & b, 2009, the extent to which water models capture non-additive interactions and cluster formation can be described by virial coefficients, which map directly onto 2-body, 3-body and higher-body interactions. These virial coefficient studies show that the rigid SPC, TIP3P, TIP4P models and the polarisable GCPM model are only in good agreement with experiment for the low-order B 2 and B 3 coefficients, whereas values obtained for B 5 and B 6 are much less accurate and applicable for a limited range of density.…”
Section: Non-additive Interactionsmentioning
confidence: 90%
“…For example, including a three-body interaction term results in very good agreement for the thermodynamic properties of argon from near the critical point to twice the critical density (Leder, 1985). As was discussed by Benjamin et al (2006Benjamin et al ( , 2007aBenjamin et al ( & b, 2009, the extent to which water models capture non-additive interactions and cluster formation can be described by virial coefficients, which map directly onto 2-body, 3-body and higher-body interactions. These virial coefficient studies show that the rigid SPC, TIP3P, TIP4P models and the polarisable GCPM model are only in good agreement with experiment for the low-order B 2 and B 3 coefficients, whereas values obtained for B 5 and B 6 are much less accurate and applicable for a limited range of density.…”
Section: Non-additive Interactionsmentioning
confidence: 90%
“…Complete description of the method is given elsewhere [6,[26][27][28][29]. However, we briefly illustrate the methodology here.…”
Section: Methodsmentioning
confidence: 99%
“…However, its success depends on the accuracy of the determination of all the virial coefficients up to the given order and convergence of the virial expansion [4]. These coefficients play a vital role in understanding the gas-phase molecular clustering phenomena in simple Lennard-Jones fluids [5] and real fluids such as water [6,7]. Virial coefficients of fluids [8][9][10][11] can be determined by a number of different experimental methods [12][13][14] and from many correlations such as due to Meng et al [15][16][17][18], and Tronopoulos [19,20] which are based on corresponding states principle.…”
Section: Introductionmentioning
confidence: 99%
“…(10). These results are of interest given the recent findings by Mhin et al (1993), Johansson et al (2005), Benjamin et al (2006) and Slanina et al (2006) who demonstrated that for neutral-water clusters (H 2 O) m at vapor saturation, there are more smaller than larger clusters at any given temperature from 300 to 646 K. We assume that this reversal in cluster abundance is due to the more endergonic binding of water in (H 2 O) m than the corresponding water attachment in the ion cluster H 3 O + Á(H 2 O) m . Note that for m = 1, binding energies for the above clusters obtained from experiment are 10.5 kJ mol À1 (Curtiss et al, 1979) and À102.2 kJ mol À1 (Likholyot et al, 2007), respectively.…”
Section: Proton-solvent Cluster Abundances In Steammentioning
confidence: 53%